Financial Soundness Indicators in Nigeria: Does Economic Condition Matters? - Nmadu, Yaaba Baba; Yakubu A., Bello; Audu, Salihu; Ibrahim, Hamman; Idrisa, Ali Gambo; Usman B., Farida (Archives of Business Research, 2020)
The growing concern amongst analysts, economists, and policy makers on the interrelationship between the soundness of the financial system and the macro-economy is gradually being confirmed by both theoretical and empirical studies. This study is an attempt to join the strand of literature that investigates the link between the soundness of the banking sector and macroeconomic performance using Nigeria’s quarterly data from 2007Q1 to 2018Q4. The study applied autoregressive distributed lag approach and found among others that FSIs are strongly related to macroeconomic variables, hence capable of pre-empting financial crisis in Nigeria. The study, therefore, recommends that movements in macroeconomic variables should be used by the Central Bank of Nigeria to take proactive supervisory policy measures to avert a systemic crisis in the banking sector.